Identifying textuality of the introduction section of academic discourse - Krishnasamy, Hariharan N.; Ishak, Mohd. Noor; Syed Sahil, Sharifah Azizah (Universiti Utara Malaysia, 1997)
The present study which attempts to look at the textuality of the introduction section focuses on three aspects that provide part of textuality specifically paragraphing language device and syntactical variation. Utilizing a combination of D' Angelo's (1977)paradigm, Lannon's (1982) categorization,Halliday & Hasan's (1976) description (with adaptation) and Umar Yunus (1989) stylistic approach, the study examined the three preceding aspects using corpus-based investigation.The corpus chosen comprise twenty articles from the International Journal of Educational Research. The Endings exhibit some dominant patterns regarding the aforementioned aspects. Pedagogical implications of the study are also discussed.